Scientometrics on Public Health Research in Iran: Increase of Area Studies despite Embargoes? A Review Article - Poreau, Brice (Iranian journal of public health, 2017)
Due to embargoes and sanctions from 1979 until 2015, impact on scientific research in Iran may be critical. Public health is the main example of this burning point. In this paper, the aim was to map the scientific research in public health in Iran until 2014 with area studies as well as networks of countries involved. We used bibliographic analyses using VOS viewer software for network analysis during the period 1975-2014. Two databases were used: Web of Science and PubMed. We performed analyses of journals, authors, publication years, organizations, funding companies, countries, keywords and Web of sciences Categories. We accessed 862 articles published between 1991 and 2014, the majority of published after 2008. The main countries of research were Iran, the United States of America, England, and Sweden and represented the main network collaboration. The main Web of Sciences categories was public, occupational and environmental health, medicine general internal and parasitology. We accessed 25462 publications on PubMed database from 1950 to 2014. The majority of published after 2004. The main area studies were prognosis, wounds and injuries, soil solutions and biological markers. Public health research in Iran has been developed since 2004. The chief field was emerging cardiovascular diseases and communicable diseases. Other biotechnological fields were emerging such as biological markers research. Iran provides structures to face up with its new challenges using networks of countries such as the USA, England, and Sweden. End of embargoes could provide new perspectives for public health research and more largely scientific research in Iran.